2021
DOI: 10.1590/1516-3180.2020.0449.r1.01102020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of scientific production on the new coronavirus (COVID-19): a bibliometric analysis

Abstract: BACKGROUND: The pandemic of the new coronavirus has culminated in a scientific race to seek knowledge about this virus and its treatments, vaccines and preventive strategies, in order to reduce its impact on healthcare and economics worldwide. Hence, it is important to recognize the efforts of researchers who are at the forefront of investigations relating to the new coronavirus. OBJECTIVE: The present study was carried out with the aim of analyzing the world scientific production relating to COVID-19. DESIGN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
(35 reference statements)
0
16
2
1
Order By: Relevance
“…In the field of COVID-19, there have been some research publications focusing on the analysis of the literature from the perspective of bibliometrics. Some of them discussed the global scientific research on COVID-19, and most of these publications analyzed the scientific productions related to COVID-19 (Costa et al, 2020;Dehghanbanadaki et al, 2020;Farooq et al, 2021;Mohadab et al, 2020;Oliveira et al, 2021). Meanwhile, in these publications, some authors summarized the hotspots and explored the future trends of the research (Gautam et al, 2020;Lou et al, 2020;Mao et al, 2020;Yang et al, 2020;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of COVID-19, there have been some research publications focusing on the analysis of the literature from the perspective of bibliometrics. Some of them discussed the global scientific research on COVID-19, and most of these publications analyzed the scientific productions related to COVID-19 (Costa et al, 2020;Dehghanbanadaki et al, 2020;Farooq et al, 2021;Mohadab et al, 2020;Oliveira et al, 2021). Meanwhile, in these publications, some authors summarized the hotspots and explored the future trends of the research (Gautam et al, 2020;Lou et al, 2020;Mao et al, 2020;Yang et al, 2020;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of country analysis, previous bibliometric studies of COVID-19 have reported a positive correlation between the number of confirmed cases and deaths and the number of COVID-19-related articles published by countries, and China ranked first in terms of both the number of articles published and number of citations, followed by the USA [25]. In the bibliometric analysis of Web of Science, PubMed, and Scopus databases, China ranked first in terms of the number of publications [26][27][28]. Furthermore, in terms of article quality, China was the top publisher of COVID-19-related articles in the top five journals-Lancet, N. Engl.…”
Section: Discussionmentioning
confidence: 86%
“…The clinical disease caused by the novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-C0V-2), is the result of a complex and ongoing battle within the body between the invading virus and the body's defense system. [ 3 4 ] Timing really matters when it comes to COVID-19 infection.…”
mentioning
confidence: 99%
“…But if a virus subverts these early defenses, the body next needs to deploy its special operation forces that have been trained through past experiences, if they had any, to fight the specific invader that the body is facing T cells. [ 3 4 ]…”
mentioning
confidence: 99%